Analysis for the Presence of Borax in IRTs and MSMEs Producing Karak in Bulu - Lucky, Lucky Sanjaya; Widyastuti, Retno; Hartati, Sri (Journal of Food and Agricultural Product, 2024)
Home Industry products and Micro, Small and Medium Enterprises (MSMEs) in the form of traditional foods are widely developed in Sukoharjo Regency. Traditional food karak crackers are one of the products favored by the people of Central Java, especially Sukoharjo Regency. Karak crackers are a food that is much loved by the community because it tastes savory, cheap and can be used for side dishes and snacks. The main ingredient in making karak crackers is poor quality rice or rice groats with added salt and bleng. Bleng is alleged to contain borax, which is harmful when it enters the human digestive system. This study aims to determine the presence of borax contained in karak crackers produced by IRTs and MSMEs in Bulu Subdistrict and to select alternative ingredients to replace bleng (borax). This research was conducted with 2 methods, namely survey and evaluation, in the survey method to determine the sample using stratified purposive sampling with 3 levels. After the karak cracker samples were collected, the presence of borax was tested using turmeric extract. The results obtained stated that all samples from IRTs and MSMEs contained borax.